De l’appropriation communautaire dans la gouvernance des pêcheries et des aires marines protégées - Moustapha Séye (VertigO)
Fisheries governance in Senegal has undergone a resurgence following international injunctions promoting Marine Protected Areas for sustainable fishing practices. Historically, artisanal fishing practices were not sufficiently regulated, leading to a loss of biodiversity and a reduction in resources. The new context is one of governance favouring the creation of marine protected areas (MPAs). The adoption of sustainable fishing practices by local populations depends on perceptions, but also on local issues and the socio-economic constraints associated with the new norm. A mixed and comparative methodology was used to gather empirical data from a survey conducted in 2014-2015 among 375 stakeholders in Saint-Louis, Kayar and Lompoul,. The study revealed that the adoption of sustainable fishing practices is influenced by local traditions of regulating fisheries resources. Localities not exposed to regulation are more inclined to promote marine protected areas. The implementation of an MPA does not guarantee the desired change in fishing practices towards sustainability. Change must be driven by the responsibility of those involved in the sector and by the application of and compliance with established standards. This perspective takes into account the principle of responsibility and the need to implement inclusive governance, in which common standards should be developed and respected by all.